2022
DOI: 10.3390/medicina58030349
|View full text |Cite
|
Sign up to set email alerts
|

Retrosternal Goitre: Anatomical Aspects and Technical Notes

Abstract: Background and Objectives: surgery for substernal goitre is still debated in the literature, due to the wide range of surgical options. This article outlines the findings of our extensive experiences, which include 264 cases of patients with “goitre plongeant“, and compares postoperative complications, despite surgical approaches. Material and Methods: preoperative planning and anatomical landmarks are described to determine the potential need of a combined approach. The surgical procedure is described, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Khairy et al (2) reported mean age of 54 years and the incidence of females was 3.3 times males. Battistella et al (5) coworkers published a study of 264 patients in more than 30 years with females 4 times males in RSG incidence and the mean age was 54years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Khairy et al (2) reported mean age of 54 years and the incidence of females was 3.3 times males. Battistella et al (5) coworkers published a study of 264 patients in more than 30 years with females 4 times males in RSG incidence and the mean age was 54years.…”
Section: Discussionmentioning
confidence: 99%
“…We did not adopt anterior thoracotomy in any of our cases. Battistella et al (5) agreed Machado that although anterior thoracotomy is an easy incision and done in supine position, but it is difficult to give a view of the right recurrent laryngeal nerve. He also denied thoracotomy as an access if the mediastinal portion is developed on the left side.…”
Section: Characteristics Of Rsgmentioning
confidence: 97%
See 3 more Smart Citations